Pengaruh Penerapan Media Pembelajaran Video Animasi terhadap Minat Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam - Dini, Dini Nur Apriyani; Imas, Imas Masruroh; Nurhayati (Journal of Teacher Training and Educational Research, 2024)
This research aims to find out how students are interested in learning and whether or not there is influence of animated video learning media on students interest in learning Islamic religious education. The method used in this research is a quantitative method and the type of research is experimental research with a population of class descriptive statistical data analysis and inferential statistic data analysis techniques. The research result obtained the average value for students was 43.68 and after the application of the animated video media the average value was 48.77. Base on the hypothesis used the paired sample t-test, is show that the significant value of the Sig value is 0.000-0.05, then Ho is rejected and Ha is accepted, which means that there's an influence of the application of animated video learning media on student learning habits in learning religious education character in class X at SMA KP 1 PASEH.